ANALISIS EFISIENSI FAKTOR PRODUKSI USAHATANI LADA DI DESA TANJUNG SETIA KECAMATAN BPR RANAU TENGAH KABUPATEN OKU SELATAN - Yunita Adelia Safitri; ema pusvita; purwadi purwadi (Program Studi Agribisnis Fakultas Pertanian Universitas Baturaja, 2023)
The purpose of this study is to analyze the factors that influence pepper production in Tanjung Setia Village, BPR Ranau Tengah District, Ogan Komering Ulu Selatan Regency and analyze the efficiency of pepper farming production factors in Tanjung Setia Village, BPR Ranau Tengah District, Ogan Komering Ulu Selatan Regency. This research was conducted with quantitative methods using primary and secondary data. Meanwhile, the data processing and data analysis method used in this research is the Cobb-Douglas . type production function analysis. The results of the study conclude that the production factors of land area, fertilizer, and labor are not efficient, so their use needs to be added. While pesticides are not efficient, it is necessary to reduce the amount for the use of pesticides.Keywords:Efficiency, Productions, Cobb-Douglas